IPTEK FAKTOR-FAKTOR YANG MEMPENGARUHI PROSES PENYELESAIAN PIUTANG NEGARA OLEH PUPN DI KPKNL MANADO - Wuwungan, Gabriela Thalia; Rawis, Sanchia Darlene; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2018)
Accounts receivable is an accounting transaction for billing consumers who are indebted to a company, an organization, or maybe to someone for goods or services that have been obtained through sales. This State's receivables occur when a person, entity or company enters into an agreement in the form of the obligation to pay to the state or body formed by the state. Management of state receivables, in the initial stages, is settled first by each institution / agency or resolved on its own internally. If the management has been handled internally but is not successful, then the receivables must be submitted to the state receivables management committee for follow-up. Procedure for managing accounts receivable is part of the process of settlement of accounts receivable. The management of this State receivable is carried out if the debtor institution or agency cannot be resolved internally. There are factors that influence and even hamper the completion of the process, including: (1) incomplete data from the debt guarantor, (2) no collateral, (3) efforts from debt insurers are not running well.Keywords : State Receivables, PUPN